Construction of an Integration Vector with a Chimeric Signal Peptide for the Expression of Monoclonal Antibodies in Mammalian Cells - Nesmeyanova, Valentina S.; Shanshin, Daniil V.; Murashkin, Denis E.; Shcherbakov, Dmitriy N. (Current Issues in Molecular Biology, 2024)
Antibodies are complex protein structures, and producing them using eukaryotic expression systems presents significant challenges. One frequently overlooked aspect of expression vectors is the nucleotide sequence encoding the signal peptide, which plays a pivotal role in facilitating the secretion of recombinant proteins. This study presents the development of an integrative vector, pVEAL3, for expressing full-length recombinant monoclonal antibodies in mammalian cells. The vector features a distinctive nucleotide sequence that encodes an artificial chimeric signal peptide with the following amino acid sequence: MMRTLILAVLLVYFCATVHC. Additionally, the vector incorporates several regulatory elements to enhance antibody expression, including the Gaussia luciferase signal sequence, internal ribosome entry site (IRES), P2A peptide, and a furin cleavage site. These elements coordinate to regulate the synthesis levels of the antibody chains. The analysis of clones obtained via transfection with the developed vector showed that over 95% of them secreted antibodies at levels significantly higher than those of the control. The immunochemical analysis of the chimeric antibody produced by the CHO-K1-10H10ch cell line confirmed the preservation of its functional activity.